Pentingnya Pendidikan Anak Usia Dini Bagi Tumbuh Kembang Anak - Salsabila Nuril Jaoza; Ageng Saepudin Kanda S (Global Leadership Organizational Research in Management, 2024)
The childhood are in gold period in along the age range human development. This period is sensitive period, during this period the children specifically receptive stimulating from the environment. At this time the children is ready doing various activity in order to understanding and mastering the environment. The gold age is period where the children start to receive various stimulation and various education efforts from their environment both intentional or unintentional. At this sensitive period occurred maturation of physical and psychic function so that ready to response and realite all development task which be expected appear at their pattern of behavior in daily. The education at childhood basically encompass all efforts and action which do educatiors and parents in treatment process, nurture, and education at children with creates an aura and the environment where the children able to explore experience which give chance to them to knowing and understand study experience which obtaining from environment, through observing, imitating, and experimenting which takes place repeatedly and involve all potential and child intelligence.